2019
DOI: 10.1186/s12891-019-2541-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in patients with sciatica: a systematic review

Abstract: Background This systematic review focusses on inflammation as an underlying pathogenic mechanism in sciatica. We addressed two questions in particular: (1) what inflammatory biomarkers have been identified in patients with sciatica in the literature so far? 2) is there an association between the level of inflammatory activity and clinical symptoms? Methods The search was conducted up to December 19th 2018 in MEDLINE, EMBASE, CENTRAL and Web of Science. The study selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
1
31
0
3
Order By: Relevance
“…19 Thus, not only do we postulate that the impaired clearance system of CSF plays a role in the pathogenesis of neurodegenerative diseases, but we also suggest that the ONSCS is often caused by MEC-induced inflammatory changes in the meninges surrounding the ON as well as in the trabeculae and septae in the ON SAS, leading to compartmentation and altered CSF dynamics. 16 Several studies 20,33,34 in dogs and humans with disc herniations demonstrated upregulation of cytokines, among them interleukin (IL)-8, but also IL-6, tumour necrosis factor-alfa and albumin. The mechanisms for these changes include mechanical irritation and cross-talk.…”
Section: Discussionmentioning
confidence: 99%
“…19 Thus, not only do we postulate that the impaired clearance system of CSF plays a role in the pathogenesis of neurodegenerative diseases, but we also suggest that the ONSCS is often caused by MEC-induced inflammatory changes in the meninges surrounding the ON as well as in the trabeculae and septae in the ON SAS, leading to compartmentation and altered CSF dynamics. 16 Several studies 20,33,34 in dogs and humans with disc herniations demonstrated upregulation of cytokines, among them interleukin (IL)-8, but also IL-6, tumour necrosis factor-alfa and albumin. The mechanisms for these changes include mechanical irritation and cross-talk.…”
Section: Discussionmentioning
confidence: 99%
“…Mivel a porckorongsérvhez és a gerincoszlop egyéb degeneratív elváltozásaihoz társuló lumbalis-lumbosacralis fájdalom patogenezisében szerepet játszik a gyulladás (1. táblázat) [13][14][15], és feltételezhető, hogy ilyen esetekben egyes gyulladásos mediátorok szintje a vérben mérhetően megemelkedik, a következőkben áttekintjük azon biomarkereket, melyekben változást találtak ebben a betegcsoportban (2. táblázat).…”
Section: áBraunclassified
“…A lumbalis-lumbosacralis fájdalom kialakulásának komponensei [13][14][15] A károsodás jellege és szintje A fájdalom oka [13].…”
Section: Táblázatunclassified
See 1 more Smart Citation
“…Twenty years later, a recent systematic review has found it difficult to "draw firm conclusions regarding the relationship between inflammation and clinical symptoms with sciatica" [2].…”
mentioning
confidence: 99%